Do I really want to know? A cognitive dissonance-based explanation of other-regarding behavior - Astrid Matthey; Tobias Regner (Games, 2011)
We investigate to what extent genuine social preferences can explain observed other-regarding behavior. In a dictator game variant subjects can choose whether to learn about the consequences of their choice for the receiver. We find that a majority of subjects showing other-regarding behavior when the payoffs of the receiver are known, choose to ignore these consequences if possible. This behavior is inconsistent with preferences about outcomes. Other-regarding behavior may also be explained by avoiding cognitive dissonance as in Konow (2000). Our experiment's choice data is in line with this approach. In addition, we successfully relate individual behavior to proxies for cognitive dissonance.
Keywords: 330; social preferences; other-regarding behavior; experiments; cognitive dissonance